Optimalisasi Peran Perawat Jiwa Melalui Online Telephone Based Counseling Di Era Digital: Studi Deskriptif Pada Rumah Sakit Jiwa Prof. HB Sa’anin Padang - Arini, Larasuci (Jurnal Keperawatan Muhammadiyah, 2025)
Objective: The development of digital technology has opened up enormous opportunities for the provision of health services, including mental health. One innovation that can improve access to psychosocial services is telephone-based counseling. This is particularly important for patients facing social stigma, physical limitations, or geographical barriers. As part of mental health services, mental health nurses play a crucial role in this counseling process. However, challenges such as non-verbal communication and limited technological training continue to hinder the optimization of these services. Methods: This quantitative descriptive study was conducted from April 12 to 16, 2025, at Prof. HB. Sa'anin Mental Hospital in Padang. Thirty-five mental health nurses were purposively selected as respondents. Data were collected through a questionnaire that measured perceptions regarding the ease of using telephone media, self-confidence levels, and barriers to implementing telephone-based counseling. Results : Most participants (57.1%) were aged between 31 and 40 years (45.7%). The results indicate that only 8.6% of respondents had ever participated in telephone-based counseling training. On average, respondents rated the use of the telephone for counseling as fairly easy (average 3.2), with a confidence level of 3.03. However, the ability to build therapeutic relationships was relatively low (2.83), indicating that there are issues with non-verbal communication. Conclusion : The results indicate that, although mental health nurses consider the telephone to be a positive counseling tool, there is still a need for better competence, especially in establishing therapeutic relationships. One of the main obstacles that must be overcome is the lack of training. Therefore, to improve service effectiveness, training in communication technology and approaches to building digital therapeutic relationships is needed.